2000
DOI: 10.1530/eje.0.1420506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activin on production and secretion of prolactin and growth hormone in cultured rat GH3 cells

Abstract: Objective: To evaluate the effect of the growth factor activin A on the secretion of prolactin (PRL) and GH in cultured GH3 cells. Methods:The concentrations of PRL and GH secreted from GH3 cells cultured in media with and without activin A were measured by RIA, and the expression of PRL mRNA and GH mRNA were analyzed using the Northern blot method. Results: Activin A significantly inhibited PRL release from GH3 cells cultured for 48 h in a dosedependent manner (activin: 0.3-3nM). The inhibitory effects of 3nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…Therefore, TRHinduced follistatin does not have a direct effect on prolactin expression, whereas follistatin affects somatolactotrophs indirectly through inhibition of activin. Previous reports have demonstrated that activin has an inhibitory effect on PRL production [46,47]. In our studies, we also showed that activin decreases PRL promoter activity and this inhibition is rescued in the presence of follistatin (Fig.…”
Section: Effects Of Follistatin On Somatolac-totroph and Gonadotrsupporting
confidence: 84%
“…Therefore, TRHinduced follistatin does not have a direct effect on prolactin expression, whereas follistatin affects somatolactotrophs indirectly through inhibition of activin. Previous reports have demonstrated that activin has an inhibitory effect on PRL production [46,47]. In our studies, we also showed that activin decreases PRL promoter activity and this inhibition is rescued in the presence of follistatin (Fig.…”
Section: Effects Of Follistatin On Somatolac-totroph and Gonadotrsupporting
confidence: 84%
“…In our study, whether MEK and p38 MAPK respectively mediated the induction of IL-6 on hGH-gene expression or interacted with each other remains to be determined. Delidow et al (1991) and Tamura et al (2000) found that the regulatory mechanism of GH and PRL-gene transcription by activin and TGF-b was independent of Pit-1 protein in GH3 cells. In this study, we also found that Pit-1 may not be involved in the stimulatory effect of IL-6 on hGHpromoter activity, although a significant number of studies showed that Pit-1 plays a pivotal role in basal and GHRHinduced GH-gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have been used previously by ourselves and others as an accepted model for studying both GH-gene expression and the molecular mechanism involved (Tamura et al 2000, Gong et al 2003a, 2003b, Adriao et al 2004.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…GH3 cells, a rat pituitary tumor cell line that secretes both GH and prolactin (PRL), was purchased from American Type Culture Collection (Manassas, Va., USA) and used for the study on GH release and regulation of expression [21, 22]. GH3 cells were maintained in Dulbecco’s modified Eagle’s Medium (Life Technologies, Grand Island, N.Y., USA) supplemented with 20% fetal bovine serum and antibiotics (100 U/ml penicillin and 100 U/ml streptomycin) in a 5% CO 2 -95% air atmosphere at 37°C.…”
Section: Methodsmentioning
confidence: 99%